2004
DOI: 10.1002/ajmg.a.30407
|View full text |Cite
|
Sign up to set email alerts
|

Mild phenotypes in a series of patients with Opitz GBBB syndrome with MID1 mutations

Abstract: Opitz syndrome (OS; MIM 145410 and MIM 300000) is a congenital midline malformation syndrome characterized by hypertelorism, hypospadias, cleft lip/palate, laryngotracheoesophageal (LTE) abnormalities, imperforate anus, developmental delay, and cardiac defects. The X-linked form (XLOS) is caused by mutations in the MID1 gene, which encodes a microtubule-associated RBCC protein. In this study, phenotypic manifestations of patients with and without MID1 mutations were compared to determine genotype-phenotype cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
1
3

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 12 publications
3
74
1
3
Order By: Relevance
“…To date, 79 OS male index cases have been published that carry mutations in the MID1 gene [Cho et al, 2006;Cox et al, 2000;De Falco et al, 2003;Ferrentino et al, 2007;Gaudenz et al, 1998;Mnayer et al, 2006;Pinson et al, 2004;Quaderi et al, 1997;Schweiger et al, 1999;Shaw et al, 2006;So et al, 2005;Winter et al, 2003] and three additional OS patients are reported here [Tania Attié-Bitach, personal communication; and our unpublished results] for a total of 82 OS index cases who carry mutations in the MID1 gene. Table 1 lists all the mutations found in the MID1 gene, their position and their putative effect on the protein product or on the transcript.…”
Section: Mid1 Mutations In Os Patientsmentioning
confidence: 70%
See 3 more Smart Citations
“…To date, 79 OS male index cases have been published that carry mutations in the MID1 gene [Cho et al, 2006;Cox et al, 2000;De Falco et al, 2003;Ferrentino et al, 2007;Gaudenz et al, 1998;Mnayer et al, 2006;Pinson et al, 2004;Quaderi et al, 1997;Schweiger et al, 1999;Shaw et al, 2006;So et al, 2005;Winter et al, 2003] and three additional OS patients are reported here [Tania Attié-Bitach, personal communication; and our unpublished results] for a total of 82 OS index cases who carry mutations in the MID1 gene. Table 1 lists all the mutations found in the MID1 gene, their position and their putative effect on the protein product or on the transcript.…”
Section: Mid1 Mutations In Os Patientsmentioning
confidence: 70%
“…The expressivity of OS clinical manifestations is highly variable [Cordero and Holmes, 1978;Cox et al, 2000;De Falco et al, 2003;Opitz et al, 1969aOpitz et al, , 1969bPinson et al, 2004;Robin et al, 1996;So et al, 2005]. The clinical signs in this disorder are due to anomalies during the formation, definition, and closure of embryonic ventral midline structures leading to hypertelorism, LTE defects, and hypospadias, present in most of the patients, as well as to other less frequent signs, such as cleft lip and/or palate, cardiac and anal abnormalities and neurological defects [De Falco et al, 2003;Pinson et al, 2004;Robin et al, 1996].…”
Section: Os Clinical Manifestations In Patients Who Carry Mid1 Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…MID1 acts as an E3 ubiquitin ligase associated to the microtubules and is implicated in the control of Phosphatase 2A protein levels Schweiger, et al, 1999;Short, et al, 2002;Trockenbacher, et al, 2001). Approximately 40 mutations have been found along the entire length of the MID1 gene in both sporadic and familial cases of OS (Cox, et al, 2000;De Falco, et al, 2003;Gaudenz, et al, 1998;Mnayer, et al, 2006;Pinson, et al, 2004;So, et al, 2005;. The expressivity of the OS symptoms is highly variable and analysis of MID1-mutated patients highlighted the presence of clinical manifestations present in almost all patients (hypertelorism, LTE defects and hypospadias) and other less frequent signs such as cleft lip and/or palate, cardiac and anal defects (De Falco, et al, 2003).…”
Section: Introductionmentioning
confidence: 99%